Design a Ku-band Rectangular Waveguide for Microwaves using HFSS - Mabroka Bobreeg; Fathia Adwep (AlQalam Journal of Medical and Applied Sciences, 2025)
Using HFSS software, rectangular waveguides, the first transmission line type utilized for small systems like radars and equipment shelters, have been examined. This study computes the characteristics and field distribution for various modes of air-filled and Teflon–filled rectangular waveguides in free space, focusing on electric and magnetic field strengths. The simulation analysis is conducted for the Ku-band with an operating frequency of 15 GHz. Theoretical analyses of two waveguides were performed and compared with the simulation results to verify accuracy. Additionally, the cutoff frequencies were determined and compared with theoretical values. The mean difference between the two waveguides was also realized, and its importance in fabricating real-world components was highlighted, making the manufacturing process easier.